Study on agronomical characteristics of several introduced cucumber (Cucumis sativus L.) genotypes - Sumiahadi, Ade; Adiwijaya, Adiwijaya (Research and Social Study Institute, 2023)
Cucumber is one of the fruit vegetables favored by the Indonesian people. Its development prospect of commercial cultivation and agribusiness management has been very promising, because the marketing opportunities are not only available domestically, but also abroad. Plant introduction is a process of introducing plants from their place of origin into a new region. This study aims to examine the agronomic characteristics of several introduced cucumber genotypes, and was conducted from October to December 2022 at the experimental field of the Faculty of Agriculture, Jakarta Muhammadiyah University. Randomized Complete Group Design (RCGD) was used with five cucumber genotypes: three introduced genotypes (MIT001, MIT002, and MIT003) and two comparator domestic varieties (Ronaldo and Mercury). The results show that the introduced genotypes produced similar vegetative growth characters to those of their comparator varieties. However, several yield components produced are lower than those of their comparator varieties, as seen from several significantly different parameters. MIT001 and MIT003 produced shorter fruit length than that of their comparator variety (Ronaldo), while MIT002 produced lower plant dry weight and fruit weight per plant than those of its comparator variety (Mercury). MIT003 was able to produce the yield components closest to those of its comparator variety. Mentimun merupakan salah satu sayuran buah yang banyak digemari oleh masyarakat Indonesia. Prospek pengembangan budidaya mentimun secara komersial dan pengelolaannya dalam skala agribisnis semakin cerah, karena peluang pemasaran tidak hanya dilakukan di dalam negeri, tetapi juga mancanegara. Introduksi tanaman merupakan suatu proses memperkenalkan tanaman dari tempat asal tumbuhnya ke suatu daerah (negara) baru. Penelitian ini bertujuan mempelajari karakteristik agronomis beberapa genotipe mentimun hasil introduksi. Penelitian ini dilaksanakan dari bulan Oktober sampai Desember 2022 di lahan percobaan Fakultas Pertanian Universitas Muhammadiyah Jakarta. Rancangan penelitian yang digunakan yaitu Rancangan Kelompok Lengkap Teracak (RKLT) dengan lima taraf genotipe mentimun, yaitu tiga genotipe introduksi (MIT001, MIT002, dan MIT003) dan dua varietas nasional sebagai pembanding (Ronaldo dan Merkuri). Hasil penelitian menunjukkan bahwa setiap genotipe introduksi yang diujikan secara umum memiliki karakter pertumbuhan vegetatif yang sama dengan varietas pembandingnya, namun memiliki beberapa karakter komponen produksi yang lebih rendah dari varietas nasional pembandingnya. Genotipe introduksi MIT001 dan MIT003 memiliki panjang buah yang lebih pendek dari varietas nasional pembandingnya (Ronaldo), sedangkan MIT002 menghasilkan bobot kering tanaman dan bobot buah per tanaman yang lebih rendah dari varietas nasional pembandingnya (Merkuri). Genotipe MIT003 adalah genotipe introduksi yang mampu menghasilkan produksi yang paling mendekati varietas pembandingnya.